Identification of Neutrophil-Related Factor LCN2 for Predicting Severity of Patients With Influenza A Virus and SARS-CoV-2 Infection - Huang, Zhisheng; Li, Hui; Liu, Shuai; Jia, Ju; Zheng, Ying; Cao, Bin (Frontiers in Microbiology, 2022)
Background: Influenza and COVID-19 are respiratory infectious diseases that are characterized by high contagiousness, high mutation and pose a serious threat to global health. After Influenza A virus (IAV) and SARS-CoV-2 infection, severe cases may develop into acute lung injury (ALI). Immune factors act as an important role during infection and inflammation. However, the molecular immune mechanisms still remain unclear. We aimed to explore immune-related host factors and core biomarker for severe infection, to provide a new therapeutic target of host factor in patients. Methods: Gene expression profiles were obtained from Gene Expression Omnibus (GEO) and the Seurat R package was used for data process of single-cell transcriptome. Differential expressed genes (DEGs) analysis, cell cluster were used to explore core host genes and source cells of genes. We performed Gene Ontology (GO) enrichment, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, and Gene set enrichment analysis (GSEA) to explore potential biological functions of genes. Gene set variation analysis (GSVA) was used to evaluate the important gene set variation score for different samples. We conduct Enzyme linked immunosorbent assay (ELISA) to test plasma concentrations of Lipocalin 2 (LCN2). Results: Multiple virus related, cytokine related, chemokine related pathways involved in process of IAV infection and inflammatory response mainly derives from macrophages and neutrophils. LCN2 mainly in neutrophils was significantly up-regulated after either IAV or SARS-CoV-2 infection, and positively correlated with disease severity. The plasma LCN2 of influenza patients were elevated significantly compared with healthy controls by ELISA and positively correlated with disease severity of influenza patients. Further bioinformatics analysis revealed that LCN2 involved in functions of neutrophils, including neutrophil degranulation, neutrophil activation involved in immune response, and neutrophil extracellular trap formation. Conclusions: The neutrophils-related LCN2 could be a promising biomarker for predicting severity of patients with IAV and SARS-CoV-2 infection and may as a new treatment target in severe patients.